2022
DOI: 10.3168/jds.2021-20691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circadian system disruption on the concentration and daily oscillations of cortisol, progesterone, melatonin, serotonin, growth hormone, and core body temperature in periparturient dairy cattle

Abstract: Metabolic, circadian, sleep, and reproductive systems are integrated and reciprocally regulated, but the understanding of the mechanism is limited. To study this integrated regulation, the circadian timing system was disrupted by exposing late pregnant nonlactating (dry) cows to chronic shifts in the light-dark phase, and rhythms of body temperature and circulating cortisol (CORT), progesterone (P4), serotonin (5HT), melatonin (MEL), and growth hormone (GH) concentrations were measured. Specifically, across 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 70 publications
(97 reference statements)
1
11
1
3
Order By: Relevance
“…In primates, the nocturnal onset of labor coincides with increased sensitivity of the pregnant uterus to oxytocin and melatonin, two hormones driving pregnancy associated uterine contractions ( Hirst et al, 1993 ; Olcese et al, 2013 ; Olcese 2014 ). Studies of sheep have shown that circadian disruption during pregnancy increased gestation length ( Gatford et al, 2019 ), and we similarly found longer gestation length in cows exposed to chronic light-dark phase shifts during the dry period ( Suarez-Trujillo et al, 2022 ). In this study we observed that cows exposed to regular 24 h light-dark cycles (control) exhibited more robust circadian rhythms of core body temperature, cortisol, and serotonin as they approached parturition.…”
Section: Circadian System Regulation Of Reproductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In primates, the nocturnal onset of labor coincides with increased sensitivity of the pregnant uterus to oxytocin and melatonin, two hormones driving pregnancy associated uterine contractions ( Hirst et al, 1993 ; Olcese et al, 2013 ; Olcese 2014 ). Studies of sheep have shown that circadian disruption during pregnancy increased gestation length ( Gatford et al, 2019 ), and we similarly found longer gestation length in cows exposed to chronic light-dark phase shifts during the dry period ( Suarez-Trujillo et al, 2022 ). In this study we observed that cows exposed to regular 24 h light-dark cycles (control) exhibited more robust circadian rhythms of core body temperature, cortisol, and serotonin as they approached parturition.…”
Section: Circadian System Regulation Of Reproductionsupporting
confidence: 59%
“…Ruminants also show food anticipatory activity, as circadian rhythms of activity and temperature similarly shifted in response to timed meal feeding in sheep and goats ( Piccione et al, 2003 , 2007 ; Giannetto et al, 2010 ). Our studies of dairy cows found evidence for a food anticipatory rise in core body temperature at three weeks before expected calving in non-lactating (dry) cows ( Suarez-Trujillo et al, 2022 ). In lactating cows, feeding time affects circadian rhythms of feeding and lying behavior, and core body temperature ( Niu et al, 2014 ).…”
Section: Integration and Reciprocal Regulation Between Circadian And ...mentioning
confidence: 68%
See 1 more Smart Citation
“…There is evidence that cattle exhibit a distinguished circadian rhythm in body temperature which fluctuates by season and reproductive stages [ 51 , 52 ]. In humans, the core body temperature reaches its lowest point at 03:00 to 06:00 a.m., completely opposite of the observed increase in melatonin synthesis [ 53 ].…”
Section: Circadian Rhythms Environmental Factors and Body Temperaturementioning
confidence: 99%
“…The circadian cycles of free-ranging nocturnal rodents are shortened under constant-dark (DD) conditions 9,10 and extended under constant-light (LL) conditions 11,12 relative to those lasting 24 h per day. Under anomalous environmental rhythms such as a 16-h light/8-h dark cycle 13 and delayed 14 or advanced 15,16 phase shifts, rodents respond by altering their circadian cycles within a certain range but may also exhibit some physiological malfunctions 17,18 . Indeed, discrepancies between environmental and internal rhythms cause stress and often lead to social and psychological disorders 6,19,20 .…”
Section: Introductionmentioning
confidence: 99%